MENINGKATKAN KEMAMPUAN MENULIS TEKS PROSEDUR MELALUI STRATEGI WRITING IN THE HERE AND NOW - Susanti, Darmiyanti; Priyadi, A. Totok; Salem, Laurensius (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis study is aimed to describe the improvement of writing abiliy on procedure text by using Writing In The Here and Now learning model at the eighth grade students of SMAN 3 Sanggau. The method used in this research was descriptive method. Descriptive method is concerned with developing or giving explanations of social phenomena towards subject that being observed. The techniques used in this research were observaion, documentary study, and test. The result of writing ability on prosedure text by using writing in the here and now learning model at the eighth grade students of SMAN 3 Sanggau in the firstcycle was 72, 88%  and in  the second cycle, the students? score was 80, 45%. It can be concluded that the implementation of Writing In The Here and Now learning  model improved students? writing ability on procedure text at the eighth grade students of senior high school in SMAN 3 Sanggau.Keywords: Writing Ability, Writing In The Here and Now, Students Outcom